Sleep efficiency changes in patients with sleep disorders after inpatient treatment: a real-world retrospective study - Ren, Jie; Xiao, Qiuxia; Zhang, Jing; Ma, Runxing; Ma, Yanyan; Li, Biao; Yang, Lan; Xiong, Liulin (Frontiers in Psychiatry, 2026)
BackgroundSleep disorders are prevalent conditions that affect both physical and mental health. Evidence describing short-term changes in sleep during hospitalization remains limited. In this study, we examined changes in sleep efficiency (SE) among hospitalized patients with sleep disorders in real-world inpatient settings and explored associated factors.MethodsWe retrospectively analyzed electronic medical records of patients with sleep disorders who received inpatient treatment at Sleep Medicine Center of Zunyi First People’s Hospital. Missing data were handled using multiple imputation. The Wilcoxon signed-rank test was used to compare pre- and post-hospitalization SE derived from sleep diaries. LASSO regression was used to identify variables associated with post-treatment SE. Multiple linear regression models and sensitivity analyses were conducted to confirm the robustness of the main results.ResultsSE improved significantly after hospitalization. LASSO regression identified six candidate predictors. The apnea–hypopnea index (AHI) showed a consistent negative relationship with post-treatment SE in the multiple imputation model. Red blood cell count (RBC) was also associated with post-treatment SE in the multiple imputation model, while other variables including triglyceride, monocyte percentage, Pittsburgh Sleep Quality Index, and Insomnia Severity Index showed limited effects.ConclusionsShort-term inpatient management was associated with significant improvement in diary-derived SE, and baseline AHI showed potential negative correlation with post-treatment SE. Further validation in larger, multi-center cohorts is needed to confirm these findings and better understand the factors influencing sleep improvement in hospitalized patients.